Karakteristik Pengguna Alun-Alun Ida Dewa Agung Jambe, Klungkung - Ningsih, Fitria Larasuwati; Kohdrata, Naniek (Nandur; Vol 3 No 4 (2023), 2023)
Alun-Alun Ida Dewa Agung Jambe is the only open public space in Klungkung Regency. This square has undergone many changes in the function of space from time to time. The government plans to organize this open public space as a community recreation facility to improve the quality of public recreation spaces. The research aims to identify the facilities, identify the characteristics of users, and provide adjustments between areas and facilities with user. It used the survey method, and the data were collected through observations, questionnaires and literature study. Then the collected data were analyzed descriptive qualitatively. The results show that the location of Alun-Alun Ida Dewa Agung Jambe is very strategic, which is located in the center of Semarapura city with various tourist objects. The results also show that Alun-Alun Ida Dewa Agung Jambe provides various areas and facilities that can be utilized free of charge. Users have characteristics that tend to visit with other people either with friends or family. The purpose of using Alun-Alun Ida Dewa Agung Jambe is recreation, sports and social interaction. The number of visits is one to two hours per week and with duration is one to two hours. Users who come to the square tend to use private vehicles like motorbike. In general, the areas and facilities provided by the Klungkung government are in accordance with the activities carried out the users.